Zika virus infection triggers lipophagy by stimulating the AMPK-ULK1 signaling in human hepatoma cells - Qin, Zhao-Ling; Yao, Qiu-Feng; Zhao, Ping; Ren, Hao; Qi, Zhong-Tian (Frontiers in Cellular and Infection Microbiology, 2022)
Zika virus (ZIKV) is a globally transmitted mosquito-borne pathogen, and no effective treatment or vaccine is available yet. Lipophagy, a selective autophagy targeting lipid droplets (LDs), is an emerging subject in cellular lipid metabolism and energy homeostasis. However, the regulatory mechanism of lipid metabolism and the role of lipophagy in Zika virus infection remain largely unknown. Here, we demonstrated that ZIKV induced lipophagy by activating unc-51-like kinase 1 (ULK1) through activation of 5' adenosine monophosphate (AMP)-activated protein kinase (AMPK) in Huh7 cells. Upon ZIKV infection, the average size and triglyceride content of LDs significantly decreased. Moreover, ZIKV infection significantly increased lysosomal biosynthesis and LD-lysosome fusion. The activities of AMPK at Thr-172 and ULK1 at Ser-556 were increased in ZIKV-infected cells and closely correlated with lipophagy induction. Silencing of AMPK expression inhibited ZIKV infection, autophagy induction, and LD-lysosome fusion and decreased the triglyceride content of the cells. The activities of mammalian target of rapamycin (mTOR) at Ser-2448 and ULK1 at Ser-757 were suppressed independently of AMPK during ZIKV infection. Therefore, ZIKV infection triggers AMPK-mediated lipophagy, and the LD-related lipid metabolism during ZIKV infection is mainly regulated via the AMPK-ULK1 signaling pathway.